Mucinous Neoplasm of the Appendix as a Mimic of Cystic Adnexal Pathology - Hutchinson, Chris; Lyske, Jonathan; Patel, Vimal; Low, Gavin
Pelvic pain presents a common diagnostic conundrum with a myriad of causes ranging from benign and trivial to malignant and emergent. We present a case where a mucinous neoplasm of the appendix acted as a mimic for tubular adnexal pathology on imaging. With the associated imaging findings on ultrasound, computed tomography, and magnetic resonance imaging, we wish to raise awareness of mucinous tumors of the appendix when tubular right adnexal pathology is present both in the presence of pelvic or abdominal pain or when noted incidentally. Tubular pathology such as uncomplicated paraovarian cysts or hydrosalpinx is frequently treated conservatively with long-interval follow-up imaging or left to clinical follow-up. Thus, if incorrectly diagnosed as tubular pathology, an appendix mucocele or mucinous neoplasm of the appendix is likely to be undertreated. We wish to clarify some of the confusion around nomenclature and classification of the multiple entities that are comprised by the terms mucocele and mucinous tumor of the appendix.